Question

39. (2) ( a^{2}+b^{2}+c^{2}=2(a-b-c)- )
( Rightarrow a^{2}+b^{2}+c^{2}-2 a+2 b+2 c+ )
( 3=0 )
( Rightarrow a^{2}-2 a+1+b^{2}+2 b+1+c^{2} )
( +2 c+1=0 )
( Rightarrow(a-1)^{2}+(b+1)^{2}+(c+1)^{2}= )
( left[text { If } x^{2}+y^{2}+z^{2}=0 Rightarrow x=0 ; y=0 ; zright. )
( =0 )
( therefore a-1=0 Rightarrow a=1 )
( b+1=0 Rightarrow b=-1 )
( c+1=0 Rightarrow c=-1 )
( therefore 2 a-3 b+4 c=2+3-4=1 )

# 39. If a + b + c = 2 (a-b-c) - 3 then the value of 2a- 3b + 4C is (1)3 (3) 2 (2) 1 (4) 4 M

Solution